Study of structure, bonding and electronic properties of derivatives of cyclohexagermanes - Welly Richartio. (2010)
The focus of this project is to study the structure, bonding and electronic properties of halogenated cyclohexagermanes. Investigations were done to give some ideas of the synthetic pathways of germanium nanowires (GeNWs), which comprise of interconnected chair cyclohexagermanes. Geometry optimizations and vibrational frequency calculations at B3LYP/6 311+G(d,p) level of theory, with zero-point vibrational energy correction were performed by means of Gaussian03 package. Three types of halogenated cyclohexagermanes were examined, i.e. Ge6H11X, Ge6H10X2 and Ge6X12. Due to the presence of high electro-negativity species, stereoelectronic effects found to outweigh steric hindrance factors. The incorporation of more halogen groups results in the decrease of Ge-X bond length. Natural bond orbital analysis confirmed that p character of Ge hybrid orbital of in σGe–X bond decreases when more X groups are incorporated, thus stronger Ge-X bond. In addition, frequency calculation revealed the nature of stationary points, which recommended more conformers in between the investigated structures to be considered, especially in the pseudo-rotation regions. As chair conformer found to be the global minima for all of the investigated derivatives, the reaction pathways to synthesis of GeNWs from halogenated cyclohexagermanes might be prospective. However, there is a trade-off between prominent quantum size effects and smaller inter-conversion barrier observed in Ge ring system.